Analysing the Bio-engineers' Growth, Reproduction, and Compost Production from Degradable Face Masks Decomposed with Medicinal Plants - Sujatha, P. S.; Pavithran, S.; Ganesan, G.; Karthik, M.; Maivizhi, V. (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
Aims: The primary objective of the study is to estimate the NPK produced in the waste disposable of a Face Mask (FM) is decomposed with a medicinal plant Lagerstroemia speciosa (LS). Background: The COVID-19 pandemic has led to a dramatic increase in the use of disposable face masks, as a critical measure to prevent virus transmission. While their role in reducing the spread of infectious diseases is undeniable, the environmental impact of disposable face masks has become a significant concern. Materials and Methods: All the experimental setup was carried out at the PG and Research Toxicology Lab, Department of Zoology, Government Arts College, Coimbatore. The experimental design consists of 5 groups; each group contains yard soil, cow dung, and coir pith as compost bedding materials. T1 - control, T2 - KWCO, T3 - FMCO, T4 - LSCO and T5 - ESLS. Results: The result shows that the growth rate of Eisenia fetida depends on the length and weight of the worms. The reproduction rate varies depending on compost materials, with higher rates in T4 and lower rates in T1. The T5 shows a high level but is a little lower than the T4. Juvenile numbers are low in T2 and T3 trials. NPK Level: The nitrogen level 413.2±2.90** is highest in T4 and T3 is 404.3±1.78. Low in T1 336.6±2.84 trial, moderate in 376.3±3.13** T2 trial and T5 consist of 372.3±2.59**. The Phosphorus is commendably high in T5 1011.3±2.59** and T1 contains 992.3±3.06. The moderate amount is in T4 894.3±2.22**. The lowest level of P 623±2.94** is in T2 and T3 contains 676.6±2.88**. The potassium amount varies in each trial. T1 is the most prominent amount of Potassium, and the level of K is 1900.3±1.18. The kitchen waste T2 trial produced 1840.6±2.37** and the amount of K is in 1670.3±1.18** T4. The most important face mask blue and black colour samples are mixed with kitchen waste T3 produces 1700±3.77** and medicinal Plant T5 which produces 1569.3±2.84**. This study found that using earthworms to promote soil amelioration can significantly improve soil quality and fertility by accelerating the decomposition process and enhancing nutrient availability. The findings have implications for sustainable agriculture and environmental management practices. Conclusion: In conclusion is that the medicinal plants had a significant effect on the growth and reproductive rate of red wrigglers, and this effect was positively correlated with the NPK level in the soil.